Determinants of Social Health Insurance Administration Body Participant Satisfication with Outpatient Installation Services - Marisi Malau; Ermi Girsang; Sri Lestari Ramadhani Nasution; Ali Napiah Nasution; Sri Wahyuni Nasution (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
This study aims to analyze the determinants that affect the satisfaction of BPJS participants with outpatient installation services at Royal Prima Marelan Hospital. Patient satisfaction is an important indicator in assessing the quality of health services, especially in the National Health Insurance (JKN) program organized by BPJS. The research method used is observational analysis with a cross-sectional approach. The research sample consisted of 232 respondents selected through the purposive sampling method, namely BPJS participant patients who visited the outpatient installation of the Royal Prima Marelan Hospital. The variables analyzed included membership status, perception of service procedures (registration), perception of human resource services (health workers), perception of drug services (pharmacy), and perception of facilities. Data collection was carried out using a structured questionnaire that included the dimensions of these services. Data analysis involves univariate tests, bivariates with chi-square tests, and multivariates to determine dominant factors. The results showed that 83.3% of respondents were satisfied with the service, while the rest felt less satisfied. The factors that had a significant relationship with patient satisfaction were perception of service procedures (p=0.004), perception of human resource services (p=0.039), perception of drug services (p=0.000), and perception of facilities (p=0.011). The perception of drug services has the greatest influence on the satisfaction of BPJS participants. These results suggest that the accuracy, availability, and ease of access of medications greatly contribute to satisfaction rates. The conclusion of this study is that improving the quality of significant service factors, especially related to drug services and facilities, needs to be a priority for hospitals to increase the satisfaction of BPJS participants. This research is expected to be a reference for policymakers in designing strategies to improve health services, especially at the Royal Prima Marelan Hospital.Keywords: Hospital, Installation Services, Outpatient, Social Health Insurance Administration